1996
DOI: 10.1212/wnl.46.4.985
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, blinded, placebo-controlled trial of divalproex sodium prophylaxis in adults with newly diagnosed brain tumors

Abstract: Anticonvulsant prophylaxis with divalproex sodium is not indicated for patients with brain tumors who have not had seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
110
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(116 citation statements)
references
References 19 publications
2
110
0
2
Order By: Relevance
“…Our data suggest that we could only rule out a risk reduction of more than 46% if patients took anticonvulsants prophylactically. However, when considered in conjunction with other randomized trials (or portions thereof 7,38,39 ), and a metaanalysis, 37 the results suggest prophylactic anticonvulsants are ineffective. The lower than expected seizure and survival rates we found in our patients suggested we needed to accrue ≥ 900 patients to have an adequately powered study; this was clearly not feasible or reasonable and we terminated the study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our data suggest that we could only rule out a risk reduction of more than 46% if patients took anticonvulsants prophylactically. However, when considered in conjunction with other randomized trials (or portions thereof 7,38,39 ), and a metaanalysis, 37 the results suggest prophylactic anticonvulsants are ineffective. The lower than expected seizure and survival rates we found in our patients suggested we needed to accrue ≥ 900 patients to have an adequately powered study; this was clearly not feasible or reasonable and we terminated the study.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Brain tumour patients who present with seizures are treated with anticonvulsants but these drugs are frequently used prophylactically. A generalized seizure may be lethal if it is prolonged or if the patient does not recover consciousness.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Randomized prospective studies have found no significant reduction in the incidence of first seizures in brain tumor patients placed on prophylactic anticonvulsants. [35][36][37] New onset of seizures was experienced by approximately 25% of patients treated with prophylactic anticonvulsants, not significantly different than the percentage of patients experiencing new onset of seizures in the control arm. The meta-analysis by Glantz et al 34 concluded that there was no evidence that prophylactic anticonvulsants significantly decreased the incidence of first seizure.…”
Section: Prophylactic Anticonvulsantsmentioning
confidence: 99%